Physico-chemical characteristics of butter prepared from the milk of selected indigenous and crossbred cows - Sathiya, Taherabbas; Ramani, Akshay; Seth, Raman; Gandhi, Kamal; Sharma, Rajan; mann, Bimlesh (Indian Journal of Dairy Science, 2024)
This study aimed to investigate the effects of the season in relation to breed and the butter preparation method on chemical composition, β-carotene content, conjugated linoleic acid (CLA) content, color attributes, texture profile, and keeping quality. Fat content showed minor variation in butter types, conventional butter had significantly (p<0.05) lower free fatty acid (FFA) levels than desi butter. Tharparkar butter, especially in summer batches, had the highest β-carotene content. CLA levels varied with breed and season, increased during summer due to outdoor grazing on green fodder. The colour analysis highlighted breed-specific variations, with Tharparkar butter displaying superior visual characteristics. Texture analysis demonstrated that conventional butter was harder, less adhesive, and showed higher cohesiveness compared to desi butter. The study emphasizes the need for careful breed selection and seasonal considerations to ensure the nutritional quality, appearance, texture, and quality of butter products. Monitoring free fatty acid levels is crucial for assessing butter shelf life and quality.